Effectiveness of Moist Wound Healing Versus Conventional Wound Care for Diabetic Ulcer Healing in Patients with Diabetes Mellitus - Grasela Lelemboto; Eko Winarto; M Jamaluddin; Fery Agusman Motuho Mendrofa (Open Access Health Scientific Journal, 2026)
Background: Diabetic ulcers are a common complication of diabetes mellitus that often occur on the legs and feet and are difficult to heal because of poor circulation and uncontrolled blood glucose, which can progress to infection and gangrene. This study aimed to compare the effectiveness of moist wound healing dressing and conventional wound care on the healing of the inflammatory phase of diabetic ulcers.Methods: A quasi-experimental, two-group pre-test post-test design was used. Thirty patients with diabetic ulcers at Yunita Wound Care, Manado, were assigned by total sampling to an experimental group (n=15, moist wound healing dressing) and a control group (n=15, conventional wound care). Inflammatory-phase healing (redness, heat, pain, swelling, functional loss) was assessed on day 1 (pre-test) and day 3 (post-test) using a validated questionnaire and analyzed with the Wilcoxon Signed Rank Test and Independent Samples T-Test.Results: Post-test scores were significantly lower in the experimental group than the control group for redness (1.47 vs 2.47, p=0.001), heat (1.33 vs 2.20, p=0.004), and swelling (1.47 vs 2.27, p=0.000). No significant between-group difference was found for pain (p=0.158) or functional loss (p=0.702).Conclusion: Moist wound healing dressing is more effective than conventional wound care in accelerating inflammatory-phase healing of diabetic ulcers, particularly in reducing redness, heat, and swelling.